Assessment of energy security of Ukraine in the implementation of renewable energy technologies (Economics and region, 2022)
The article investigates the definition of indicators of effective assessment of energy security of Ukraine in the implementation of renewable energy technologies based on SWOT analysis. Priority of implementation of technologies using energy of renewable sources on leveling of threats to energy supply of the country is defined. The scientific and methodological approach to assessment of innovative development of Ukraine in the system of energy security using a modified model of SWOT analysis is substantiated. The advantage of the model is compactness of development due to the use of a single platform and efficiency of use due to the absence of the need to reload data into a specialized system. With the help of fractal analysis, a graphical interpretation of the comparison of SWOT analysis components in the innovative development of Ukraine in the system of energy security is built. The peculiarity of the proposed model lies in the fact that the data, having both qualitative and quantitative characteristics, are subject to analysis. As a conclusion, it is proposed to carry out an economic analysis of the factors influencing the prioritization of key technologies in the Ukrainian industry.
Keywords: security; energy saving; SWOT analysis; innovation; development